MO342: Impact of COVID-19 Pandemic on In-Hospital Acute Kidney Injury Epidemiology and Outcomes: A Retrospective Cohort Study. (3rd May 2022) - Esposito, Pasquale; Russo, Elisa; Picciotto, Daniela; Cappadona, Francesca; Battaglia, Yuri; Battista Traverso, Giovanni; Viazzi, Francesca
Abstract: BACKGROUND AND AIMS: Acute kidney injury (AKI) is a common complication in patients affected by coronavirus disease-19 (COVID-19) and its development is associated with high mortality [1 ]. However, it is also clear that the COVID-19 pandemic has effects on the management of diseases not directly related to COVID-19 [2 ]. In this study, we investigated the impact of the COVID-19 pandemic on general intrahospital AKI incidence and outcomes. METHOD: We performed a retrospective cohort study comparing data on AKI epidemiology and outcomes of patients hospitalized from January 2016 to December 2019 (pre-COVID-19 period) and from January to December 2020 (COVID-19 period, including both SARS-CoV-2 negative and positive patients). AKI was defined and classified by evaluating the kinetics of intra-hospital creatinine (comparing the peak to the minimum serum creatinine level, considered as the basal value) [3 ]. The prevalence of chronic kidney disease (CKD) (i.e. eGFR < 60 mL/min) was calculated in patients with previous creatinine values available. Patients with CKD stage 4–5 (i.e. eGFR < 30 mL/min/1.73 m 2 ) and with a length of hospital stay > 30 days were excluded. RESULTS: A total of 51 681 patients during the pre-COVID-19 period and 10, 062 during the COVID-19 period (9026 SARS-CoV-2 negative and 1036 SARS-CoV-2 positive patients) were analysed. Patients admitted in the COVID-19 period were significantly older, with a higher prevalence of males and a reduced prevalence of chronic conditions. In-hospital AKI incidence was 31.7% during the COVID-19 period (30.5% in SARS-CoV-2 negative patients and 42.2% in SARS-CoV-2 positive ones) as compared with 25.9% during the pre-COVID-19 period ( P < .0001) (Fig. 1 ). Similarly, the COVID-19 period showed an increase in AKI stage 2–3 incidence both for AKI on CKD and for 'de novo AKI'. In multivariate analysis, demographic characteristics, length of hospital stay, ICU admission, main comorbidities, basal sCr, admission period (pre-COVID-19 or COVID-19) and SARS-CoV-2 infection were significantly associated with the risk of AKI. In particular, the admission in the COVID-19 period increased the risk of AKI [OR 1.18, 95% confidence interval (95% CI) 1.12–2.25] regardless of SARS-CoV-2 infection. Moreover, we found that in the COVID-19 period, there was an increased number of patients admitted to ICU, accompanied by a significant increase in the length of hospital stay and intrahospital mortality. In the multivariate analysis, development of AKI, admission in the COVID-19 period and active SARS-CoV-2 infection remained significantly and independently associated with mortality risk (Fig. 2 ). CONCLUSION: Overall, we found that AKI was more common and severe in the COVID-19 period, regardless of SARS-CoV-2 infection, when compared with patients admitted to the same hospital during the four years before the pandemic. So, we provide evidence that the COVID-19 pandemic has changed general in-hospital AKI epidemiology. These findings call attention to the need to adapt the resources dedicated to the prevention and management of the intra-hospital AKI in response to health emergencies.